Yttrium oxide coatings for plasma processing chamber components
By using yttrium oxide powder to form and annealed aerosol coating on the plasma treatment chamber components, the problem of insufficient etch resistance in the prior art is solved, the etch resistance and density of the components are significantly improved, and the pollution is reduced and erosion.
Patent Information
- Application Number
- CN202380043029.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-26
- Filing Date
- 2023-05-17
- Publication Date
- 2025-01-07
AI Technical Summary
The existing plasma processing chamber components are insufficient etch resistance during plasma etching, resulting in the problems of contamination and particle shedding, especially in textured components.
Yttrium oxide powder is used to form a coating through aerosol deposition technology and annealed to ensure that the coating is at least 95% pure yttrium oxide, improving the density and etch resistance of the coating.
By improving the density and etch resistance of the coating, the pollution after plasma etching and particle shedding are reduced, the etch resistance of the components is enhanced, and the erosion rate and the generation of pollutants are reduced.
Smart Images

Figure CN119278496A_ABST
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims the benefit of priority to U.S. Application No. 63 / 346,043, filed on May 26, 2022, the entire contents of which are incorporated herein by reference for all purposes. Background Art
[0002] The present disclosure relates generally to the manufacture of semiconductor devices. More particularly, the present disclosure relates to plasma chamber components used in the manufacture of semiconductor devices.
[0003] During semiconductor wafer processing, a plasma processing chamber is used to process semiconductor devices. The plasma processing chamber is affected by the plasma, which may degrade components in the plasma processing chamber. Components of the plasma processing chamber degraded by the plasma may be a source of contamination. Ceramic aluminum oxide (aluminum oxide (Al2O3)) is a material commonly used for components in plasma processing chambers because aluminum oxide tolerates plasma etching to some extent. However, the plasma etching tolerance of aluminum oxide is still insufficient.
[0004] The background description provided here is for the purpose of generally presenting the background of the present disclosure. The work of the currently designated inventors within the scope described in this background section and aspects of the specification that were not determined to be prior art at the time of filing the application are neither explicitly nor implicitly admitted to be prior art against the present disclosure. Summary of the invention
[0005] To achieve the foregoing and the purpose of the present disclosure, a plasma processing chamber component is provided herein. A yttria coating is formed on the surface of the component body, wherein the yttria coating is deposited by aerosol deposition and is annealed, wherein the yttria coating is at least 95% pure yttria by weight.
[0006] In another implementation, the component body is suitable for use in a plasma processing chamber. An aerosol deposited coating of yttria powder is deposited on the component body, wherein the aerosol deposited coating is at least 95% yttria by weight. The aerosol deposited coating is annealed.
[0007] These and other features of the present disclosure will be described in more detail below in the detailed description of the invention and in conjunction with the following figures. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] The present disclosure is illustrated by way of example and not limitation in the accompanying figures and in which like reference numerals indicate similar elements and in which:
[0009] Figure 1A high-level flowchart of the implementation scheme.
[0010] Figure 2A-2C is a schematic diagram of components processed according to an embodiment.
[0011] Figure 3 is a schematic diagram of a plasma processing chamber that may be used in embodiments. DETAILED DESCRIPTION
[0012] The present invention will now be described in detail with reference to several preferred embodiments shown in the accompanying drawings. In the following description, many specific details are set forth in order to provide a thorough understanding of the present invention. However, it will be apparent to those skilled in the art that the present invention can be implemented without some or all of these specific details. In other cases, known process steps and / or structures are not described in detail to avoid making the present invention unclear unnecessarily.
[0013] Aerosol deposition (AD) coating technology remains a commonly used method for producing "plasma or etch resistant" coatings on chamber components. However, as manufacturers move to future technology nodes and increasingly stringent standards are implemented for particles; particle generation remains the primary failure mode for such barrier coatings. Smooth versions of AD coated components tend to have weak areas at the end regions, i.e., the edges of the coating. For certain components that require texturing, the texturing will generally cause particles to fall off more easily because the coating is less dense (texturing is difficult to achieve on a fully dense coating).
[0014] According to some embodiments described herein, components of a plasma processing chamber are provided with a more etch-resistant coating deposited using yttrium oxide (Y2O3) (also known as yttria) powder.
[0015] To promote understanding, Figure 1 is a high-level flow chart of a process used in an embodiment. A component body is provided (step 104). Figure 2A 204 is a schematic cross-sectional view of a component body 204 used in an embodiment. In certain embodiments, the component body 204 comprises a ceramic material. In certain embodiments, the component body 204 is made of ceramic alumina. In certain embodiments, the ceramic alumina component body 204 is a dielectric power window. In certain embodiments, a bore 206 passes through the center of the power window to provide a gas injector.
[0016] Yttrium oxide powder is provided (step 108). In this example, the yttrium oxide powder is at least 95% pure by weight. In certain embodiments, the average particle size of the yttrium oxide powder falls within the range of 40 nm to 50 nm.
[0017] Next, an aerosol deposition coating of yttrium oxide powder is deposited on the surface of the component body 204 (step 112). The aerosol deposition is accomplished by passing a carrier gas through a fluidized bed of solid yttrium oxide powder. Driven by the pressure difference, the yttrium oxide powder particles are accelerated through the nozzle, and an aerosol jet is formed at its outlet. Next, the aerosol is directed to the surface of the component body 204, where the aerosol jet impacts the surface at a high speed. The powder mixture particles are broken into solid nano-scale fragments, thereby forming a coating. Optimization of the type of carrier gas, gas consumption, spray distance (standoff distance) and scanning speed provides a high-quality coating. As described above, aerosol deposition can be performed at room temperature. Figure 2B is a schematic cross-sectional view of a component body 204 after aerosol deposition of an AD coating 208 on which yttria powder has been deposited.
[0018] After depositing the AD coating 208 (step 112), the AD coating 208 can be provided with an optional coating conditioning treatment (step 114). For example, in certain embodiments, the AD coating 208 can be cleaned and ground. In certain embodiments, the cleaning can include brushing the entire window surface with a 3000 grit abrasive to remove the grinding slurry and loose particles or debris. Next, brushing can be performed, followed by solid CO2 blasting to remove any remaining loose features and / or brushing residues. Deionized water can then be used for precision wet cleaning. Next, the window can be baked.
[0019] Next, the AD coating 208 is annealed (step 116). In this embodiment, the AD coating is heated to a temperature in the range of 650°C to 890°C. In certain embodiments, the AD coating is heated to a temperature in the range of 700°C to 850°C. The annealing temperature is maintained below 900°C to prevent some yttrium oxide from combining with aluminum oxide to form yttrium aluminum oxide compounds. The formation of yttrium aluminum oxide compounds will increase porosity, resulting in reduced corrosion resistance in the termination area. By maintaining the annealing temperature below 900°C, the coating maintains at least 95% pure yttrium oxide by weight. In certain embodiments, the annealing treatment provides a maximum temperature for 4 to 12 hours. In addition, in order to prevent the component body 204 from cracking, the temperature is heated and cooled at a rate of no more than 30°C per hour. In certain embodiments, the annealing is performed in an atmosphere where oxygen may be available and present. Figure 2Cis a cross-sectional image of the AD coating after the AD coating is annealed to form an annealed coating 212. Grain size measurements using a transmission electron microscope revealed that the annealing treatment has increased the average grain size from a range of 40 nm to 50 nm to a range of 70 nm to 100 nm. In certain embodiments, the annealing results in a 1.5 to 2.5 times increase in grain size. In certain embodiments, a transmission electron microscope electron backscattering (TEM-EBS) process can be used to measure the average grain size. In addition, X-ray diffraction is a method for determining the average size of single crystalline nanoparticles or grains in a nanocrystalline host material. The Scherrer equation relates the size of a crystallite in a solid to the broadening of a peak (or peaks) in a diffraction pattern. The Scherrer equation is D hkl =Kλ / (B hkl cosθ), where D hkl = crystallite size in the direction perpendicular to the lattice plane, hkl = Miller indices of the plane being analyzed, K is a numerical factor often called the grain shape factor, λ is the wavelength of the X-ray, B hkl is the width of the X-ray diffraction peak (full width at half maximum) expressed in radians, and θ is the Bragg angle.
[0020] In certain embodiments, the annealed coating 212 is at least 95% (by weight) pure yttrium oxide, has a porosity of less than 1% by volume, and has an average thickness between 5 microns and 20 microns. In certain embodiments, the annealed coating 212 is at least 99% (by weight) pure yttrium oxide.
[0021] After the AD coating 208 is annealed (step 116), optional conditioning can be provided to the annealed coating 212 (step 114). For example, the annealed coating 212 can be brushed, followed by spraying, and then a final cleaning. In certain embodiments, the spraying of the annealed coating 212 can be performed by spraying the annealed coating 212 using refrigerated carbon dioxide. When the annealing process causes grain growth, the annealing may cause some grains to protrude so that they are weakly connected, or grains may be squeezed out when surrounding grains grow, resulting in flaking. The cleaning process can be used to remove any loose particles on the annealed coating 212 that may be caused by the annealing process to reduce contaminants. Certain embodiments may use a cleaning process similar to the cleaning process provided after applying the AD coating.
[0022] Post annealing of a component having an AD coating 208 provides the possibility to "tune" the internal grain structure and porosity to achieve specific material morphology / properties. Post annealing provides a way to adjust the grain size of the AD yttria coating 208 by promoting grain growth. Coating density will improve with grain growth; with the added effect of grain fusion (reducing inter-grain porosity). Grain roughening at the surface layer (propagated by annealing) can change the surface roughness and microporosity. In addition, annealing can reduce internal stresses in the AD yttria coating 208, thereby mitigating cracking / debonding.
[0023] Since the annealing treatment increases density, reduces porosity, and increases grain size, the overall effect can result in a reduction in the rate at which the coating may be eroded by hydrochloric acid (HCl). In certain embodiments, the AD coating 208 subjected to 5 mass % HCl before annealing roughened from a roughness range of about 10 nm to 20 nm to a roughness range of about 60 nm to 100 nm in about 3 minutes. In certain embodiments, the annealed coating 212 remained within a roughness range of 10 nm to 20 nm after exposure to HCl for up to 30 minutes. The HCl test shows that the annealing makes the coating more resistant to corrosion.
[0024] The component body 204 is installed in a plasma processing chamber (step 120). In the illustrated example, the component body 204 is installed in the plasma processing chamber as a dielectric inductive power window. The plasma processing chamber is used to process a substrate (step 124), wherein plasma is generated in the chamber to process the substrate, such as etching the substrate, and the annealed coating 212 is exposed to the plasma. The annealed coating 212 provides enhanced etch resistance to protect the component body 204.
[0025] Figure 3An example of a plasma processing chamber 300 used in the embodiment is schematically shown. The plasma processing chamber 300 includes a plasma reactor 302, in which there is a plasma processing confinement chamber 304. A plasma power supply 306 regulated by a matching network 308 provides power to a transformer coupled plasma (TCP) coil 310 located near a dielectric inductive power window 312 to generate a plasma 314 in the plasma processing confinement chamber 304 by providing inductively coupled power. A pinnacle 372 extends from a chamber wall 376 of the plasma processing confinement chamber 304 to the dielectric inductive power window 312 to form a pinnacle ring. The pinnacle 372 is angled relative to the chamber wall 376 and the dielectric inductive power window 312, so that the inner angle between the pinnacle 372 and the chamber wall 376 and the inner angle between the pinnacle 372 and the dielectric inductive power window 312 are each greater than 90° and less than 180°. As shown, the pinnacle 372 provides an angled ring near the top of the plasma processing confinement chamber 304. The TCP coil (upper power supply) 310 can be configured to produce a uniform diffusion profile within the plasma processing confinement chamber 304. For example, the TCP coil 310 can be configured to produce a toroidal power distribution in the plasma 314. A dielectric inductive power window 312 is provided to separate the TCP coil 310 from the plasma processing confinement chamber 304 while allowing energy to be transferred from the TCP coil 310 to the plasma processing confinement chamber 304. The wafer bias power supply 316 regulated by the matching network 318 supplies power to the electrode 320 to set a bias voltage on the substrate 366. The substrate 366 is supported by the electrode 320. The controller 324 controls the plasma power supply 306 and the wafer bias power supply 316.
[0026] The plasma power supply 306 and the wafer bias power supply 316 can be configured to operate at a specific radio frequency, such as, for example, 13.56 megahertz (MHz), 27 MHz, 2 MHz, 60 MHz, 400 kilohertz (KHz), 2.54 gigahertz (GHz), or a combination thereof. The plasma power supply 306 and the wafer bias power supply 316 can be appropriately sized to supply a range of powers to achieve the desired processing performance. For example, in one embodiment, the plasma power supply 306 can supply a power range of 50 watts to 5000 watts, and the wafer bias power supply 316 can supply a bias range of 20 volts (V) to 2000 V. In addition, the TCP coil 310 and / or the electrode 320 can include two or more sub-coils or sub-electrodes. The TCP coil 310 and / or the electrode 320 can be powered by a single power supply, or by multiple power supplies.
[0027] like Figure 3As shown, the plasma processing chamber 300 also includes a gas source / gas supply mechanism 330. The gas source 330 is fluidly connected to the plasma processing confinement chamber 304 through a gas inlet such as a gas injector 340. The gas injector 340 can be located at any advantageous position in the plasma processing confinement chamber 304 and can be formed in any form for injecting gas. However, the gas inlet can preferably be configured to produce an "adjustable" gas injection profile. The adjustable gas injection profile allows the corresponding gas flow rates to multiple regions in the plasma processing confinement chamber 304 to be independently adjusted. More preferably, the gas injector is mounted to the dielectric induction power window 312. In such an example, the gas injector can be mounted on the power window, mounted in the power window, or form a part of the power window. The process gas and byproducts are removed from the plasma processing confinement chamber 304 by a pressure control valve 342 and a pump 344. The pressure control valve 342 and the pump 344 are also used to maintain a specific pressure in the plasma processing confinement chamber 304. The pressure control valve 342 can maintain a pressure of less than 1 Torr during processing. Edge ring 360 is placed around substrate 366. Gas source / gas supply mechanism 330 is controlled by controller 324. Kiyo manufactured by Lam Research Corp. (Fremont, CA) may be used to practice embodiments.
[0028] In various embodiments, the component can be other components of the plasma processing chamber, such as confinement rings, edge rings, Corvus rings, electrostatic chucks (ESCs), grounding rings, chamber liners, door liners, inner electrodes / showers, outer electrodes, other components that can deliver radio frequency (RF) energy, crosses, sleeves, pins, nozzles, syringes, forks, arms, etc. Other components of other types of plasma processing chambers can also be used. For example, in an embodiment, the plasma repelling ring on the bevel etching chamber can be coated. In another example, the plasma processing chamber can be a dielectric processing chamber or a conductor processing chamber. In some embodiments, the component body 204 is made of a ceramic material. In other embodiments, the component body 204 is made of a silicon (Si) material. In some embodiments, one or more but not all surfaces are coated.
[0029] In certain embodiments, the component is an inductive power window 312 having a gas injector 340, wherein the gas injector 340 passes through the perforation 206 of the inductive power window 312. In such an embodiment, the annealed coating 212 is Figure 3 The outer edge of the induction power window 312 shown in FIG. Figure 2C The termination region 220 shown, and the Figure 3 The inner edge of the perforation 206 used in the gas injector 340 shown in FIG. Figure 2CThe termination region 224 shown. The unannealed coating has a higher porosity at the termination region than the rest of the coating. Higher porosity leads to more erosion and more contaminants caused by erosion. Since the gas injector 340 is located above the center of the wafer, the termination region near the gas injector will lead to more contaminant particles near the center of the wafer. It has been found that such contaminant particles increase near the center of the wafer. Annealing of the coating reduces erosion and contaminant particles near the center of the wafer. Since certain embodiments improve the erosion resistance at the termination point where the coating is more susceptible to erosion, certain embodiments provide more uniform erosion resistance throughout the coating, including the termination region. Since annealing causes grain growth, annealing also reduces the voids that cause pits because crystal growth closes the pits. In certain embodiments, the coating at the termination region has a density of at least 95% by volume. In certain embodiments, the coating at the termination region has a density of at least 99% by volume. In certain embodiments, the coating at the termination region has a porosity of less than 1% by volume. The HCl test mentioned above helps indicate this low porosity.
[0030] Although the present invention has been described according to several preferred embodiments, there are changes, permutations, modifications and various alternative equivalents that fall within the scope of the present invention. It should also be noted that there are many alternatives to the method and apparatus of the present invention. Therefore, the following appended claims are intended to be interpreted as including all such changes, permutations and various alternative equivalents that fall within the true spirit and scope of the present invention.
Claims
1. A component of a plasma processing chamber, comprising: Component body; as well as A yttria coating is located on the surface of the component body, wherein the yttria coating is deposited by aerosol deposition and is annealed, wherein the yttria coating is at least 95% pure yttria by weight.
2. The component according to claim 1, wherein The average yttrium oxide grain size of the yttrium oxide coating is in the range of 70 nm to 100 nm.
3. The component according to claim 1, wherein The yttria coating is annealed at a maximum temperature in the range of 650°C to 900°C.
4. The component according to claim 1, wherein The component body is formed from a ceramic material.
5. The component according to claim 1, wherein The component body forms a power window.
6. The component according to claim 1, wherein The yttria coating has a porosity of less than 1% by volume.
7. The component according to claim 1, wherein: The component body forms at least one power window.
8. The component according to claim 1, wherein The yttria coating at the termination region has a porosity of less than 1% by volume.
9. A method comprising: providing a component body, the component body being suitable for use in a plasma processing chamber; depositing an aerosol deposited coating of yttrium oxide powder on the component body, wherein the aerosol deposited coating is at least 95% yttrium oxide by weight; as well as The aerosol deposited coating is annealed.
10. The method of claim 9, wherein said annealing said aerosol deposited coating comprises annealing said aerosol deposited coating at a maximum temperature in a range of 650°C to 900°C.
11. The method of claim 9, wherein the aerosol deposited coating has an average yttria grain size in the range of 70 nm to 100 nm.
12. The method of claim 9, wherein providing a component body comprises forming a ceramic component body.
13. The method of claim 9, wherein providing a component body comprises forming a power window.
14. The method of claim 9, wherein said annealing said aerosol deposited coating is provided in the presence of oxygen.
Citation Information
Cited By
Passivated perfluoroether elastomer rubber, preparation method and application
CN120624985A
Passivated perfluoroether elastomer rubber, method of making and use
CN120624985B